Search 75,719 tutors
FIND TUTORS
Ask a question
0 0

2x-4/7=x-1/9

Tutors, please sign in to answer this question.

2 Answers

The best method for solving this is to cross-multiply (which is the same as multiplying both sides by 63 and then dividing). 

You will then have:

     9(2x - 4)  = 7(x - 1)

 or      18x - 36  =  7x - 7

Now subtract 7x from both sides:

            18x - 36 = 7x - 7
             -7x           -7x
--------------------------------------
            11x - 36 =  -7

Add 36 to both sides:

            11x - 36  =  -7
                   + 36    +36
_____________________

                 11x     =   29

Now divide by 11:

                 11x/11  = 29/11

or                   x  =  29/11

 

Hello Rebecca,

For this problem use the cross multiplication. Multiply (2x - 4) by 9 and (x - 1) by 7.

Next, use distributive property and get rid of brackets, you'll get 18x - 36 = 7x - 7

Now you need to isolate the variable x. For that subtract 7x from both sides of the equation. You'll get

11x - 36 = -7

Now, add 36 on both sides of the equation.

11x = 29

Divide both sides by 11

x = 29/11 (answer)

Hope this helps you.